Technologies And Strategies For Providing Education Throughopen And Distance Learning System At Remote Regions In Indonesia(Case Study At Pontianak, West Kalimantan, Indonesia) - Isdianto, Joko (STISOSPOL WASKITA DHARMA, 2014)
As we know that technology helps many people in the world whatever their fields. One of the main benefit of the technology is the helping distance teaching and learning. Technology here is the main support for the educational development in the most remote regions in Indonesia. Many people use the advanced technologies, such as internet, as the main wares of the educational development. They promote the using of internet in many schools in Indonesia, specially in remote regions, such as remote regions in Sumatera, Kalimantan, Sulawesi and Papua. Today, most of the students in such remote regions always have fun in their study with internet as the advanced technology. Technology has enchaned teaching and learning method in Indonesia, Specially in remote region. Many Students has used advanced technology, such as computer in the classroom, new website, interactive key board, Blog and wikis, in this case, Web 2.0 that implemented in the class, so the students can have much more dialogues, digest dialogues, ideas and brainstorming. Beside that kinds, wireless michrophone, mobile and digital game, also to be the other alternatives of the advanced technologies in enchanced teaching and learning sys tem. Distance educational system by using advanced technologies make the goal of international education system become more achievable and more accessible to all students. Here, Technology has more contributions to the enchanced teaching and learning system, like what display in this site: SlideShare Here, Online tutorial is the most favourable mechanism for providing education through Open and Distance Learning System all over the world. Online tutorial gives the students so many things and choices for learning, beginning from the materials of studies, the choices of b ooks shopping, various literatures at online library, various kind of friends for communicating between one student to another. So, Technologies and Online Learning Strategies can provide education through Open and Distance Learning System at Remote Region s in Indonesia.